Prevalence of anxiety and depression in South Asia during COVID-19: A systematic review and meta-analysis. Issue 4 (April 2021) - Hossain, Md Mahbub; Rahman, Mariya; Trisha, Nusrat Fahmida; Tasnim, Samia; Nuzhath, Tasmiah; Hasan, Nishat Tasnim; Clark, Heather; Das, Arindam; McKyer, E. Lisako J.; Ahmed, Helal Uddin; Ma, Ping
Abstract: Introduction: The COVID-19 pandemic has impacted biopsychosocial health and wellbeing globally. Pre-pandemic studies suggest a high prevalence of common mental disorders, including anxiety and depression in South Asian countries, which may aggravate during this pandemic. This systematic meta-analytic review was conducted to estimate the pooled prevalence of anxiety and depression in South Asian countries during the COVID-19 pandemic. Method: We systematically searched for cross-sectional studies on eight major bibliographic databases and additional sources up to October 12, 2020, that reported the prevalence of anxiety or depression in any of the eight South Asian countries. A random-effects model was used to calculate the pooled proportion of anxiety and depression. Results: A total of 35 studies representing 41, 402 participants were included in this review. The pooled prevalence of anxiety in 31 studies with a pooled sample of 28, 877 was 41.3% (95% confidence interval [CI]: 34.7–48.1, I 2 = 99.18%). Moreover, the pooled prevalence of depression was 34.1% (95% CI: 28.9–39.4, I 2 = 99%) among 37, 437 participants in 28 studies. Among the South Asian countries, India had a higher number of studies, whereas Bangladesh and Pakistan had a higher pooled prevalence of anxiety and depression. No studies were identified from Afghanistan, Bhutan, and Maldives. Studies in this review had high heterogeneity, high publication bias confirmed by Egger's test, and varying prevalence rates across sub-groups. Conclusion: South Asian countries have high prevalence rates of anxiety and depression, suggesting a heavy psychosocial burden during this pandemic. Clinical and public mental health interventions should be prioritized alongside improving the social determinants of mental health in these countries. Lastly, a low number of studies with high heterogeneity requires further research exploring the psychosocial epidemiology during COVID-19, which may inform better mental health policymaking and practice in South Asia. Abstract : COVID-19; Mental health; Anxiety; Depression; South Asia; Afghanistan; Bangladesh; Bhutan; India; Maldives; Nepal; Pakistan; Sri Lanka; Psychiatry; Epidemiology.